FORMATISASI ONTOLOGI MANAJEMEN DAKWAH - ., Fahriansyah (Alhadharah: Jurnal Ilmu Dakwah, 2017)
When viewed in terms of elements of da'wah combined with the ontology of general management, the study area of da'wah management as a whole is 80 format. And when viewed in terms of the combination  of  da'wah interaction with the ontology of general management, then obtained  96  formulation format, so that the total format of ontology of da'wah management is 176 formulations ontology format.